2014
DOI: 10.1186/1471-2407-14-109
|View full text |Cite
|
Sign up to set email alerts
|

MiR-378 is an independent prognostic factor and inhibits cell growth and invasion in colorectal cancer

Abstract: BackgroundMicroRNAs(miRNAs) are small non-coding RNAs that participate in a variety of biologic processes, and dysregulation of miRNA is always associated with cancer development and progression. Aberrant expression of miR-378 has been found in some types of cancer. However, effects and potential mechanisms of miR-378 in colorectal cancer (CRC) have not been explored.MethodsQuantitative RT-PCR was performed to evaluate miR-378 levels in CRC cell lines and 84 pairs of CRC cancer and normal adjacent mucosa. Kapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
73
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(81 citation statements)
references
References 29 publications
7
73
1
Order By: Relevance
“…Zheng et al (2014) indicated that downregulation of miR-132 in CRC was associated with tumor size, distant metastasis, and TNM stage. Furthermore,, and miR-378a-5p expressions were identified as independent prognostic factors for CRC (Yu et al, 2013;Zhang et al, 2014a). miR-129 sensitized CRC cells to 5-FU both in vitro and in vivo (Karaayvaz et al, 2013), and miR-124 increased the radiosensitivity of CRC cells (Zhang et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Zheng et al (2014) indicated that downregulation of miR-132 in CRC was associated with tumor size, distant metastasis, and TNM stage. Furthermore,, and miR-378a-5p expressions were identified as independent prognostic factors for CRC (Yu et al, 2013;Zhang et al, 2014a). miR-129 sensitized CRC cells to 5-FU both in vitro and in vivo (Karaayvaz et al, 2013), and miR-124 increased the radiosensitivity of CRC cells (Zhang et al 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs pair with the messages of protein-coding genes to direct post-transcriptional repression [3] and target mRNAs based on sequence complementarity with target 3′-untranslated regions (3′-UTRs), leading to translational repression and/or to mRNA cleavage [4]. miRNAs are involved in cell differentiation [5], apoptosis [6], cell proliferation [7,8], division [9], protein secretion [10], immune regulation [11], viral infection [12], cancer development [13,14], invasion [15,16], tissue morphogenesis and growth [17,18], angiogenesis [19,20] and metastasis [21]. The largest functional group of miRNAs are those miRNAs involved in cancer development, and among these, some have been reported to function as oncogenic miRNAs or tumor suppressors, whereas others exert diverse functions [22].…”
Section: Introductionmentioning
confidence: 99%
“…By binding to the 3' UTRs of target genes, miRNAs play important roles in tumor pathogenesis. The expression of miR-378 is known to be downregulated in both plasma and tumor tissue in CRC patients (Zanutto et al, 2014;Zhang et al, 2014a). Overexpression of miR-378 can inhibit cell growth and invasion, while its downregulation may promote these processes (Zhang et al, 2014a), suggesting that this miRNA may function as a tumor suppressor in CRC.…”
Section: Discussionmentioning
confidence: 99%